Observations made while recreating a native Hawaiian forest - Griffin-Noyes, Emory (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2012)
Since 2007 staff at Limahuli Preserve have been developing practices to effectively reintroduce native plants into a highly degraded environment, creating a forest high in diversity and a safe habitat for some of the rarest plant species on the planet. Initial efforts were focused on the Limahuli Valley and limited progress was made because of the exposed conditions and prevalence of weed species. Relocation of the project to areas with tree cover has resulted in greater success. These successes have been built on to extend the project to the reintroduction of rare and endangered species. The methods used to transform a habitat where non-native and weed species dominate to one in which native, including endangered, species thrive is described. The value of staff with horticultural knowledge and experience of the habitat and climate is stated and ideas for the future of the habitat at Limahuli Preserve are given.